Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2018)
Corneal cross-linking as a treatment for keratoconus four-year morphologic and clinical outcomes with respect to patient age Vinciguerra R, Romano MR, Camesasca FI, Azzolini C, Orth ST, Morenghi E, Vinciguerra P Ophthalmology 2013; 120: 908–16 Effect of corneal collagen cross-linking on corneal innervation, corneal sensitivity, and tear function of patients with keratoconus Kontadakis GA, Kymionis GD, Kankariya VP, Pallikaris AI Ophthalmology 2013; 120: 917–22 Displacement of the retina and its recovery after vitrectomy in idiopathic epiretinal membrane Nitta E, Shiraga F, Shiragami C, Fukuda K, Yamashita A, Fujiwara A Am J Ophthalmol. 2013; 155: 1014–20 Excimer laser phototherapeutic keratectomy in eyes with corneal stromal dystrophies with and without a corneal graft Reddy JC, Rapuano CJ, Nagra PK, Hammersmith KM Am J Ophthalmol. 2013; 155: 1111–8.